A Measurement System for the Position and Phase Errors of the Elements in an Antenna Array Subject to Mutual Coupling. (12th February 2012) - Lindgren, Tore; Borg, Johan
Abstract : When deploying large antenna arrays in arctic environments, a local measurement system may be necessary in order to ensure control over the position and phase of the individual antenna elements. In this paper, a method of estimating the position and phase of each individual antenna element in the presence of mutual coupling is presented. It uses both measurements of the scattering matrix in the array and measurements of the electric field using a minimum of four probes located in the near field of the array. Simulations show that the method gives accurate results even in the presence of noise in the measurements. The geometry of the probe-array system affects the performance significantly.